Analysis of ChatGPT Usage to Support Student Lecture Assignments - Randa Liling, Jenary; Anas Aklani, Syaeful (JURNAL FASILKOM, 2023)
Technology is revolutionizing the way education is delivered, making it more accessible, efficient, and effective than ever before. The pace of technological advancement in the educational sector is accelerating at an unprecedented rate, transforming the traditional classroom model, and empowering learners with new tools and resources to enhance their learning experience. One such technology is artificial intelligence, such as ChatGPT. This artificial intelligence technology developed by OpenAI is increasingly being utilized in educational settings, particularly to assist students in completing their academic tasks. This study aims to analyze and understand the perspectives of students regarding the use of ChatGPT, an AI-powered chatbot, as an aid in their academic coursework. The research employs both quantitative and qualitative approaches based on the Technology Acceptance Model (TAM), and data analysis is conducted using PLS-SEM. The results indicate that the research variable "Perceived Usefulness" has a significant influence on students' attitudes towards the use of ChatGPT. Additionally, the variable "Attitude towards ChatGPT" significantly impacts students' intention to use ChatGPT as a tool to assist them with academic tasks in the future. These findings provide valuable insight into the potential benefits of ChatGPT as an educational tool and highlight the importance of students' perceptions and attitudes towards technology in shaping their academic experiences.